Self-repairing material for photovoltaic cable and preparation method of self-repairing material

By using β-cyclodextrin and adamantane carboxylic acid to form a supramolecular network, combined with mechanical fusion modified polypropylene, the problem of poor self-repair performance of photovoltaic cables is solved, and the self-healing and environmental protection performance improvement is achieved without external stimulation factors.

CN119613861APending Publication Date: 2025-03-14曾玉峰
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411801791.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The self-repair performance of existing photovoltaic cables is poor, making it difficult to achieve repeated repairs, and most self-repair materials require external stimulation factors to activate self-repair characteristics, affecting the self-healing efficiency of the material.

Method used

β-cyclodextrin and adamantane carboxylic acid are used as the host and guest to form a supramolecular network through polar attraction to achieve self-healing of the material, and modify polypropylene through mechanical fusion to improve the flexibility and environmental protection of the material.

Benefits of technology

It realizes that photovoltaic cables automatically identify damage and achieve self-healing without external stimulation factors, improves the environmental performance and impact resistance of the material, and extends the service life of the cable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005178220790000081
    Figure BDA0005178220790000081
  • Figure BDA0005178220790000082
    Figure BDA0005178220790000082
Patent Text Reader

Abstract

The invention discloses a self-repairing material for a photovoltaic cable and a preparation method of the self-repairing material, and belongs to the technical field of cable preparation. Beta-cyclodextrin and adamantane carboxylic acid are added when the self-repairing material is prepared, so that the self-repairing material can automatically identify damage or sense structural defects, and the damage self-healing property of the self-repairing characteristic of the photovoltaic cable can be activated without external stimulation factors. By modifying polypropylene, the environmental protection performance of the photovoltaic cable can be effectively improved, the aging rate and the breakage rate can be reduced, and the high-molecular compound and polypropylene can enable the photovoltaic cable to have good toughness, do not have a cracking phenomenon, and also have good impact resistance and environmental protection performance; the anti-ultraviolet shielding agent can provide ultraviolet shielding performance for the photovoltaic cable, so that the photovoltaic cable can still operate safely in a severe environment. The self-healing rate of the prepared self-repairing material can reach 85.5% at most, the use requirements of users can be met, and the service life of the photovoltaic cable is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of cable preparation, and in particular relates to a self-repairing material for photovoltaic cables and a preparation method thereof. Background Art

[0002] Photovoltaic cables, as the core of power transmission in solar photovoltaic power generation facilities, will be directly related to the safety, reliability and advancement of solar photovoltaic power generation systems. Photovoltaic cables need to be laid outdoors in harsh environmental conditions. They are easily affected by climate and ultraviolet rays during installation and operation. Ultraviolet radiation causes photo-oxidative degradation, resulting in polymer chain breakage, free radical formation and molecular weight reduction. These changes lead to the deterioration of the mechanical properties of the cables, which further causes insufficient ultraviolet protection, affects the service life of the cables and even causes damage. Therefore, in order to reduce the aging and damage rate of photovoltaic cables, the development of self-repairing insulating materials is an urgent problem to be solved. However, the repair ability of existing self-repairing materials is limited, and it is difficult to achieve repeated repair. In addition, most of the repair materials require external stimuli (such as heat, light, pH, etc.) to activate the self-repairing properties, which hinders the self-healing efficiency of the materials. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a self-repairing material for photovoltaic cables and a preparation method thereof, so as to solve the technical problem that the self-repairing performance of existing cables is poor.

[0004] In order to achieve the above object, the technical solution adopted by the present invention is: to provide a method for preparing a self-repairing photovoltaic cable, comprising the following steps:

[0005] S1. adamantane carboxylic acid and thionyl chloride are mixed, stirred and reacted at 80-100°C for 4-6 hours, then hydroxyethyl methacrylate is added and the reaction is continued for 30-60 minutes, and finally washed and filtered, and the filtrate is dried at 75-85°C for 6-10 hours to obtain Ad-HEMA; the ratio of adamantane carboxylic acid, thionyl chloride and hydroxyethyl methacrylate is 2-3 g: 40-60 mL: 0.5-1.5 mL;

[0006] S2, dissolving β-cyclodextrin in water, then adding p-toluenesulfonyl chloride and alkali, reacting at 20-25°C for 1-2h, then filtering, adjusting the pH value of the filtrate to 7-8, and finally standing at 2-6°C for 10-14h to obtain TOS-CD; the mass ratio of β-cyclodextrin, p-toluenesulfonyl chloride and alkali is 8-12:2-3:3-5;

[0007] S3, dispersing Al2O3 nanoparticles in an organic solvent, then adding TOS-CD and mixing evenly, then adjusting the pH value of the mixture to 7-8, and reacting at 60-70°C for 10-14h under the protection of inert gas, and finally filtering and washing to obtain CD-Al2O3 NPs; the mass ratio of Al2O3 nanoparticles to TOS-CD is 1-5:25-50;

[0008] S4, dispersing CD-Al2O3 NPs in an organic solvent, then adding Ad-HEMA, stirring at room temperature for 22-26 hours, then adding a polymer compound, stirring at 75-200°C for 20-40 minutes, then standing for 8-12 hours, and finally drying at 150-200°C for 6-12 hours to obtain a polymer blend; the mass ratio of CD-Al2O3 NPs, Ad-HEMA and polymer compound is 1-5:4-8:10-15;

[0009] S5, mixing the polymer blend and polypropylene in a mass ratio of 1-5:10-15, stirring at 180-250° C. for 10-30 min, then standing for 3-5 h, and finally drying at 60-120° C. for 12-24 h to obtain a polymer composite;

[0010] S6, mixing the polymer composite and the anti-ultraviolet shielding agent evenly, then heating to 60-90°C, adding ammonium sulfate solution and stirring to react for 30-60 minutes, and finally drying at 200-280°C for 10-14 hours to obtain a self-healing intermediate; the ratio of the polymer composite, the anti-ultraviolet shielding agent and the ammonium sulfate solution is 10-20g:1-3g:30-50mL;

[0011] S7. Mix the self-healing intermediate, the vulcanizing agent and the vulcanization accelerator in a mass ratio of 2-3:4-6:1-2, and then react at 180-200° C. for 10-30 min to obtain a self-healing material.

[0012] Among the above components, the self-healing material is synthesized through the host-guest inclusion model with β-cyclodextrin as the host and adamantane carboxylic acid as the guest. The β-cyclodextrin molecule has a lipophilic cavity inside, and the adamantane carboxylic acid molecule exhibits excellent lipophilicity. The two are combined through polar attraction. In addition, the cavity size of β-cyclodextrin is 0.7-0.8nm, and the diameter of the adamantane carboxylic acid molecule is about 0.7nm. The host and guest molecules are completely matched in size, which means that adamantane carboxylic acid can enter the cavity of β-cyclodextrin. When the material is damaged, the self-healing material can automatically identify damage or sense structural defects, and based on the lipophilic cavity of β-cyclodextrin and the lipophilic structure of adamantane, the adamantane is stuck in the cavity of the cyclodextrin molecule through the same polar attraction, forming a stable supramolecular network, realizing the self-healing property of the material.

[0013] The host-guest assembly is prepared by free radical copolymerization of polymer compounds with adamantane carboxylic acid and β-cyclodextrin to obtain a self-healing material with suitable mechanical strength. Its self-healing performance is mainly due to the existence of non-covalent bonds and does not require external stimulation to activate the self-healing properties. It is a special supramolecular material based on the host-guest interaction model.

[0014] Polypropylene (PP) is a typical thermoplastic polymer. With its excellent heat resistance, electrical properties and degradability, it has become the preferred material for the main insulation of new environmentally friendly cables. Traditional polypropylene materials have the disadvantages of high hardness, high crystallinity and low flexibility, which cannot meet the fundamental requirements of photovoltaic cables. Therefore, in the research field of insulating materials, the modification of PP cable materials is the fundamental to change its performance. The present invention uses mechanical fusion to mix polypropylene with polymer blends, improves the flexibility of polypropylene, increases the environmental protection and self-healing properties of the polymer composite, and adds an anti-ultraviolet shielding agent to the polymer matrix to provide the material with the ability to shield ultraviolet light.

[0015] On the basis of the above technical solution, the present invention can also be improved as follows:

[0016] Furthermore, the base is NaOH or KOH.

[0017] Furthermore, the organic solvent is dimethyl sulfoxide (DMSO) or N,N-dimethylformamide (DMF).

[0018] Furthermore, the inert gas is nitrogen or argon.

[0019] Furthermore, the polymer compound is at least one of polyvinyl pyrrolidone (PVP), hydroxyethyl methacrylate (HEMA), acrylate (AE), ethylene glycol dimethacrylate (EGDMA), azobisisobutyronitrile (AIBN), ethylene-vinyl acetate copolymer (EVA), polyether polyol (POP) and polyolefin elastomer (POE).

[0020] Furthermore, the anti-ultraviolet shielding agent is TiO2, ZnO, SiO2 or CeO2.

[0021] Further, the concentration of the ammonium sulfate solution is 0.013-0.1 mol / L.

[0022] Furthermore, the vulcanizing agent is benzoyl peroxide (BPO) or diethylpropene peroxide (DCP); and the vulcanization accelerator is trimethylolpropane trimethacrylate (TMPTMA) or tetramethylthiuram disulfide (TMTD).

[0023] The invention also discloses a self-repairing material prepared by the preparation method.

[0024] The invention also discloses the application of the self-repairing material in the preparation of photovoltaic cables.

[0025] The beneficial effects of the present invention are as follows: β-cyclodextrin and adamantane carboxylic acid are added when preparing the self-healing material, so that it can automatically identify damage or sense structural defects, and realize the self-healing property of the photovoltaic cable without the need for external stimulation factors to activate the self-healing property. By modifying polypropylene, the environmental performance of the photovoltaic cable can be effectively improved, the aging and breakage rate can be reduced, and the polymer compound and polypropylene can make the photovoltaic cable have good toughness, will not crack, and also have good impact resistance and environmental protection; the anti-ultraviolet shielding agent can provide the photovoltaic cable with the performance of shielding ultraviolet rays, so that it can still operate safely in harsh environments. The self-healing rate of the self-healing photovoltaic cable prepared by the present invention can reach up to 85.5%, which can meet the user's use needs and extend the service life of the photovoltaic cable. DETAILED DESCRIPTION

[0026] The specific embodiments of the present invention are described below to facilitate the understanding of the present invention by those skilled in the art. If the specific conditions are not specified in the examples, the methods are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturers are not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially. However, it should be clear that the present invention is not limited to the scope of the specific embodiments. For those skilled in the art, as long as various changes are within the spirit and scope of the present invention defined and determined by the attached claims, these changes are obvious, and all inventions and creations using the concept of the present invention are protected.

[0027] Example 1

[0028] A method for preparing a self-repairing material for a photovoltaic cable comprises the following steps:

[0029] S1. Mix 2.5 g of adamantane carboxylic acid and 50 mL of thionyl chloride, and react with stirring at 90° C. for 5 h to obtain adamantane carboxyl chloride; then dissolve the adamantane carboxyl chloride in 30 mL of CH2Cl2 solution, add 100 mL of CH2Cl2, 1 mL of hydroxyethyl methacrylate (HEMA) and 1.6 mL of triethylamine, and continue to react for 45 min. Finally, wash with 1 mol / L hydrochloric acid solution, sodium bicarbonate and deionized water in sequence, filter, and dry the filtrate at 80° C. for 8 h to obtain Ad-HEMA;

[0030] S2, dissolving 50g of β-cyclodextrin (β-CD) in 1.2L of deionized water, then adding 13g of p-toluenesulfonyl chloride (TOS-Cl) and 20g of NaOH or KOH, reacting at 22°C for 1.5h, then filtering to remove excess p-toluenesulfonyl chloride, adjusting the pH value of the filtrate to 8 with ammonium chloride, and finally standing at 4°C for 12h, filtering to obtain TOS-CD;

[0031] S3, 0.5 g Al2O3 nanoparticles (NH2-Al2O3 NPs) were dispersed in 25 mL dimethyl sulfoxide (DMSO) and stirred for 30 min, then 8 g TOS-CD was added and mixed evenly, then the pH value of the mixture was adjusted to 8, then nitrogen was introduced into the reaction system for protection, and the reaction was carried out at 65 ° C for 12 h, and finally filtered, and the filtrate was washed with ethanol to obtain CD-Al2O3NPs;

[0032] S4, 0.3g CD-Al2O3 NPs were dispersed in 3mL N,N-dimethylformamide (DMF) and ultrasonicated for 30min, then 0.6g Ad-HEMA was added, stirred at room temperature for 24h, then 0.6g polyvinyl pyrrolidone (PVP), 0.5g hydroxyethyl methacrylate (HEMA), 2.37mL acrylate (AE), 0.5μL ethylene glycol dimethacrylate (EGDMA) and 0.72mg azobisisobutyronitrile (AIBN) were added, stirred at 150℃ for 30min and then allowed to stand for 10h, finally placed in a vacuum drying oven and dried at 175℃ for 9h to remove the solvent to obtain a polymer blend;

[0033] S5, 0.3 g of the polymer blend and 1.4 g of polypropylene (PP) were mixed, stirred at 210° C. for 20 min, then allowed to stand for 4 h, and finally dried at 90° C. for 18 h to obtain a polymer composite containing polypropylene;

[0034] S6. Mix 1g of a high molecular weight composite containing polypropylene and 0.1g of TiO2 evenly, then heat to 82°C, add 4mL of an ammonium sulfate solution with a concentration of 0.05mol / L, and stir to react for 45min. Finally, place the reaction mixture in a vacuum drying oven and dry at 240°C for 12h to obtain a self-healing intermediate.

[0035] S7. The self-healing intermediate, benzoyl peroxide (BPO) and trimethylolpropane trimethacrylate (TMPTMA) were mixed in a mass ratio of 5:10:3, and then reacted at 190° C. for 20 minutes to obtain a self-healing material.

[0036] Example 2

[0037] A method for preparing a self-repairing material for a photovoltaic cable comprises the following steps:

[0038] S1. Mix 2 g of adamantane carboxylic acid and 60 mL of thionyl chloride, and react with stirring at 80°C for 6 h to obtain adamantane carboxyl chloride; then dissolve the adamantane carboxyl chloride in 30 mL of CH2Cl2 solution, add 100 mL of CH2Cl2, 1.5 mL of hydroxyethyl methacrylate (HEMA) and 1.6 mL of triethylamine, and continue to react for 30 min. Finally, wash with 1 mol / L hydrochloric acid solution, sodium bicarbonate and deionized water in sequence, filter, and dry the filtrate at 85°C for 6 h to obtain Ad-HEMA;

[0039] S2, dissolving 50 g of β-cyclodextrin (β-CD) in 1.2 L of deionized water, then adding 13 g of p-toluenesulfonyl chloride (TOS-Cl) and 20 g of KOH, reacting at 20°C for 2 h, then filtering to remove excess p-toluenesulfonyl chloride, adjusting the pH value of the filtrate to 7 with ammonium chloride, and finally standing at 2°C for 10 h, filtering to obtain TOS-CD;

[0040] S3, 0.5 g Al2O3 nanoparticles (NH2-Al2O3 NPs) were dispersed in 25 mL dimethyl sulfoxide (DMSO) and stirred for 30 min, then 5 g TOS-CD was added and mixed evenly, then the pH value of the mixture was adjusted to 7, then argon was introduced into the reaction system for protection, and the reaction was carried out at 70 ° C for 10 h, and finally filtered, and the filtrate was washed with ethanol to obtain CD-Al2O3NPs;

[0041] S4, 0.3 g CD-Al2O3 NPs were dispersed in 3 mL N,N-dimethylformamide (DMF) and ultrasonicated for 30 min, then 0.6 g Ad-HEMA was added, stirred at room temperature for 22 h, and then 1 g ethylene-vinyl acetate copolymer (EVA) was added, stirred at 200 ° C for 20 min and then allowed to stand for 8 h, and finally placed in a vacuum drying oven and dried at 200 ° C for 6 h to remove the solvent to obtain a polymer blend;

[0042] S5, 0.3 g of the polymer blend and 1.5 g of polypropylene (PP) were mixed, stirred at 180° C. for 30 min, then allowed to stand for 3 h, and finally dried at 60° C. for 24 h to obtain a polymer composite containing polypropylene;

[0043] S6, 1g of the polymer composite containing polypropylene and 0.3g of ZnO were mixed evenly, then the temperature was raised to 60°C, and 5mL of ammonium sulfate solution with a concentration of 0.013mol / L was added and stirred for reaction for 60min, and finally the reaction mixture was placed in a vacuum drying oven and dried at 280°C for 10h to obtain a self-healing intermediate;

[0044] S7. The self-healing intermediate, diethylpropyl peroxide (DCP) and tetramethylthiuram disulfide (TMTD) were mixed in a mass ratio of 2:6:1, and then reacted at 180°C for 25 minutes to obtain a self-healing material.

[0045] Example 3

[0046] A method for preparing a self-repairing material for a photovoltaic cable comprises the following steps:

[0047] S1. Mix 2.5 g of adamantane carboxylic acid and 50 mL of thionyl chloride, and react with stirring at 100 °C for 4 h to obtain adamantane carboxyl chloride; then dissolve the adamantane carboxyl chloride in 30 mL of CH2Cl2 solution, add 100 mL of CH2Cl2, 1 mL of hydroxyethyl methacrylate (HEMA) and 1.6 mL of triethylamine, and continue to react for 60 min. Finally, wash with 1 mol / L hydrochloric acid solution, sodium bicarbonate and deionized water in sequence, filter, and dry the filtrate at 75 °C for 6 h to obtain Ad-HEMA;

[0048] S2, 60g of β-cyclodextrin (β-CD) was dissolved in 1.2L of deionized water, followed by the addition of 15g of p-toluenesulfonyl chloride (TOS-Cl) and 15g of NaOH, and the mixture was reacted at 25°C for 1h, and then the excess p-toluenesulfonyl chloride was removed by filtration, and the pH value of the filtrate was adjusted to 7.5 with ammonium chloride, and finally the mixture was allowed to stand at 6°C for 14h, and filtered to obtain TOS-CD;

[0049] S3, 0.5 g Al2O3 nanoparticles (NH2-Al2O3 NPs) were dispersed in 25 mL dimethyl sulfoxide (DMSO) and stirred for 30 min, then 16 g TOS-CD was added and mixed evenly, then the pH value of the mixture was adjusted to 7.5, then argon gas was introduced into the reaction system for protection, and the reaction was carried out at 60 ° C for 14 h, and finally filtered, and the filtrate was washed with ethanol to obtain CD-Al2O3NPs;

[0050] S4, 0.3 g CD-Al2O3 NPs were dispersed in 3 mL N,N-dimethylformamide (DMF) and ultrasonicated for 30 min, then 0.6 g Ad-HEMA was added, stirred at room temperature for 22-26 h, and then 1.5 g polyether polyol (POP) was added, stirred at 75 ° C for 40 min and then allowed to stand for 12 h, and finally placed in a vacuum drying oven and dried at 150 ° C for 12 h to remove the solvent to obtain a polymer blend;

[0051] S5, 0.5 g of the polymer blend and 1.4 g of polypropylene (PP) were mixed, stirred at 250° C. for 10 min, allowed to stand for 5 h, and finally dried at 120° C. for 12 h to obtain a polymer composite containing polypropylene;

[0052] S6, 1g of the polymer composite containing polypropylene and 0.2g of SiO2 were mixed evenly, then the temperature was raised to 90°C, and 3mL of ammonium sulfate solution with a concentration of 0.1mol / L was added and stirred for reaction for 30min, and finally the reaction mixture was placed in a vacuum drying oven and dried at 200°C for 14h to obtain a self-healing intermediate;

[0053] S7. The self-healing intermediate, benzoyl peroxide (BPO) and tetramethylthiuram disulfide (TMTD) were mixed in a mass ratio of 3:6:2, and then reacted at 200°C for 30 minutes to obtain a self-healing material.

[0054] Example 4

[0055] A method for preparing a self-repairing material for a photovoltaic cable comprises the following steps:

[0056] S1. Mix 3 g of adamantane carboxylic acid and 40 mL of thionyl chloride, and react with stirring at 80°C for 4 h to obtain adamantane carboxyl chloride; then dissolve the adamantane carboxyl chloride in 30 mL of CH2Cl2 solution, add 100 mL of CH2Cl2, 0.5 mL of hydroxyethyl methacrylate (HEMA) and 1.6 mL of triethylamine, and continue to react for 60 min. Finally, wash with 1 mol / L hydrochloric acid solution, sodium bicarbonate and deionized water in sequence, filter, and dry the filtrate at 75°C for 10 h to obtain Ad-HEMA;

[0057] S2, dissolving 40 g of β-cyclodextrin (β-CD) in 1.2 L of deionized water, then adding 10 g of p-toluenesulfonyl chloride (TOS-Cl) and 25 g of KOH, reacting at 25°C for 2 h, then filtering to remove excess p-toluenesulfonyl chloride, adjusting the pH value of the filtrate to 7 with ammonium chloride, and finally standing at 2°C for 14 h, filtering to obtain TOS-CD;

[0058] S3, 0.5 g Al2O3 nanoparticles (NH2-Al2O3 NPs) were dispersed in 25 mL dimethyl sulfoxide (DMSO) and stirred for 30 min, then 3 g TOS-CD was added and mixed evenly, then the pH value of the mixture was adjusted to 8, then argon was introduced into the reaction system for protection, and the reaction was carried out at 60 ° C for 10 h, and finally filtered, and the filtrate was washed with ethanol to obtain CD-Al2O3NPs;

[0059] S4, 0.3 g CD-Al2O3 NPs were dispersed in 3 mL N,N-dimethylformamide (DMF) and ultrasonicated for 30 min, then 0.6 g Ad-HEMA was added, stirred at room temperature for 22 h, and then 1.2 g polyolefin elastomer (POE) was added, stirred at 75 ° C for 20 min and then allowed to stand for 8 h, and finally placed in a vacuum drying oven and dried at 150 ° C for 10 h to remove the solvent to obtain a polymer blend;

[0060] S5, 0.3 g of the polymer blend and 1 g of polypropylene (PP) were mixed, stirred at 180° C. for 10 min, then allowed to stand for 3 h, and finally dried at 100° C. for 20 h to obtain a polymer composite containing polypropylene;

[0061] S6, 1.5g of the polymer composite containing polypropylene and 0.1g of CeO2 were mixed evenly, then the temperature was raised to 90°C, 4mL of ammonium sulfate solution with a concentration of 0.08mol / L was added, and the mixture was stirred for reaction for 60min, and finally the reaction mixture was placed in a vacuum drying oven and dried at 230°C for 14h to obtain a self-healing intermediate;

[0062] S7. The self-healing intermediate, diethylpropene peroxide (DCP) and trimethylolpropane trimethacrylate (TMPTMA) are mixed in a mass ratio of 2:4:1, and then reacted at 200°C for 10 minutes to obtain a self-healing material.

[0063] Comparative Example 1

[0064] A method for preparing a photovoltaic cable comprises the following steps:

[0065] S1. Dissolve 50 g of β-cyclodextrin (β-CD) in 1.2 L of deionized water, then add 13 g of p-toluenesulfonyl chloride (TOS-Cl) and 20 g of NaOH or KOH, react at 22°C for 1.5 h, then filter to remove excess p-toluenesulfonyl chloride, adjust the pH value of the filtrate to 8 with ammonium chloride, and finally stand at 4°C for 12 h, filter, and obtain TOS-CD;

[0066] S2, 0.5 g Al2O3 nanoparticles (NH2-Al2O3 NPs) were dispersed in 25 mL dimethyl sulfoxide (DMSO) and stirred for 30 min, then 8 g TOS-CD was added and mixed evenly, then the pH value of the mixture was adjusted to 8, then nitrogen was introduced into the reaction system for protection, and the reaction was carried out at 65 ° C for 12 h, and finally filtered, and the filtrate was washed with ethanol to obtain CD-Al2O3NPs;

[0067] S3, 0.3 g CD-Al2O3 NPs were dispersed in 3 mL N,N-dimethylformamide (DMF) and ultrasonicated for 30 min, then 0.6 g polyvinyl pyrrolidone (PVP), 0.5 g hydroxyethyl methacrylate (HEMA), 2.37 mL acrylate (AE), 0.5 μL ethylene glycol dimethacrylate (EGDMA) and 0.72 mg azobisisobutyronitrile (AIBN) were added, stirred at 150 ° C for 30 min and then allowed to stand for 10 h, and finally placed in a vacuum drying oven and dried at 175 ° C for 9 h to remove the solvent to obtain a polymer blend;

[0068] S4, 0.3 g of the polymer blend and 1.4 g of polypropylene (PP) were mixed, stirred at 210° C. for 20 min, then allowed to stand for 4 h, and finally dried at 90° C. for 18 h to obtain a polymer composite containing polypropylene;

[0069] S5, 1g of the polymer composite containing polypropylene and 0.1g of TiO2 were mixed evenly, then the temperature was raised to 82°C, 4mL of 0.05mol / L ammonium sulfate solution was added, and the mixture was stirred for reaction for 45min, and finally the reaction mixture was placed in a vacuum drying oven and dried at 240°C for 12h to obtain an intermediate;

[0070] S6. The intermediate, benzoyl peroxide (BPO) and trimethylolpropane trimethacrylate (TMPTMA) were mixed in a mass ratio of 5:10:3, and then reacted at 190° C. for 20 minutes to obtain a sheath layer material.

[0071] Comparative Example 2

[0072] A method for preparing a photovoltaic cable comprises the following steps:

[0073] S1. Mix 2.5 g of adamantane carboxylic acid and 50 mL of thionyl chloride, and react with stirring at 90° C. for 5 h to obtain adamantane carboxyl chloride; then dissolve the adamantane carboxyl chloride in 30 mL of CH2Cl2 solution, add 100 mL of CH2Cl2, 1 mL of hydroxyethyl methacrylate (HEMA) and 1.6 mL of triethylamine, and continue to react for 45 min. Finally, wash with 1 mol / L hydrochloric acid solution, sodium bicarbonate and deionized water in sequence, filter, and dry the filtrate at 80° C. for 8 h to obtain Ad-HEMA;

[0074] S2, 0.5 g of Al2O3 nanoparticles (NH2-Al2O3 NPs) were dispersed in 25 mL of dimethyl sulfoxide (DMSO) and stirred for 30 min, then the pH value of the mixture was adjusted to 8, and then nitrogen was introduced into the reaction system for protection, and the reaction was carried out at 65 ° C for 12 h, and finally filtered, and the filtrate was washed with ethanol to obtain intermediate 1;

[0075] S3, 0.3g of intermediate 1 was dispersed in 3mL N,N-dimethylformamide (DMF) and ultrasonicated for 30min, then 0.6g of Ad-HEMA was added, stirred at room temperature for 24h, then 0.6g of polyvinyl pyrrolidone (PVP), 0.5g of hydroxyethyl methacrylate (HEMA), 2.37mL of acrylate (AE), 0.5μL of ethylene glycol dimethacrylate (EGDMA) and 0.72mg of azobisisobutyronitrile (AIBN) were added, stirred at 150°C for 30min and then allowed to stand for 10h, finally placed in a vacuum drying oven and dried at 175°C for 9h to remove the solvent to obtain a polymer blend;

[0076] S4, 0.3 g of the polymer blend and 1.4 g of polypropylene (PP) were mixed, stirred at 210° C. for 20 min, then allowed to stand for 4 h, and finally dried at 90° C. for 18 h to obtain a polymer composite containing polypropylene;

[0077] S5, 1g of the polymer composite containing polypropylene and 0.1g of TiO2 were mixed evenly, then the temperature was raised to 82°C, and 4mL of 0.05mol / L ammonium sulfate solution was added and stirred for 45min, and finally the reaction mixture was placed in a vacuum drying oven and dried at 240°C for 12h to obtain intermediate 2;

[0078] S6. The intermediate dibenzoyl peroxide (BPO) and trimethylolpropane trimethacrylate (TMPTMA) were mixed in a mass ratio of 5:10:3, and then reacted at 190° C. for 20 minutes to obtain a sheath layer material.

[0079] Experimental example

[0080] The commercially available irradiated cross-linked polyethylene material (purchased from Zhejiang Wanma Polymer Material Co., Ltd.) was used as a control group, and the self-healing material prepared in Examples 1-4 and the sheath layer material prepared in Comparative Examples 1 and 2 were cut as experimental samples. After the cutting was completed, the cut surface was spliced ​​and repaired for 2 hours. Finally, the fracture strength of the sample before and after cutting was tested. The self-healing rate was evaluated based on the pre-fracture strength of the sample material before and after cutting, and the evaluation results are shown in Table 1. The calculation formula of the self-healing rate is as follows:

[0081]

[0082] Table 1 Comparison of self-healing rate data of sample materials

[0083]

[0084] As can be seen from Table 1, the fracture strength of the self-healing material prepared in the embodiment of the present invention has a significant difference before and after cutting, and its self-healing rate can reach up to 85.5%, which has an excellent self-healing effect. When β-cyclodextrin or adamantane carboxylic acid is omitted, a supramolecular network structure cannot be formed in the sheath layer material. When the material is damaged, the sheath layer material cannot automatically identify damage or sense structural defects, and the self-healing property of the material cannot be achieved.

Claims

1. A method for preparing a self-healing material for photovoltaic cables, characterized in that: The following steps are involved: S1. adamantane carboxylic acid and thionyl chloride are mixed, stirred and reacted at 80-100° C. for 4-6 hours, then hydroxyethyl methacrylate is added and the reaction is continued for 30-60 minutes, and finally washed and filtered, and the filtrate is dried at 75-85° C. for 6-10 hours to obtain Ad-HEMA; the ratio of adamantane carboxylic acid, thionyl chloride and hydroxyethyl methacrylate is 2-3 g: 40-60 mL: 0.5-1.5 mL; S2, dissolving β-cyclodextrin in water, then adding p-toluenesulfonyl chloride and alkali, reacting at 20-25°C for 1-2h, then filtering, adjusting the pH value of the filtrate to 7-8, and finally standing at 2-6°C for 10-14h to obtain TOS-CD; the mass ratio of β-cyclodextrin, p-toluenesulfonyl chloride and alkali is 8-12:2-3:3-5; S3, dispersing Al2O3 nanoparticles in an organic solvent, then adding TOS-CD and mixing evenly, then adjusting the pH value of the mixed solution to 7-8, and reacting at 60-70°C for 10-14h under the protection of inert gas, and finally filtering and washing to obtain CD-Al2O3 NPs; the mass ratio of the Al2O3 nanoparticles to TOS-CD is 1-5:25-50; S4, dispersing CD-Al2O3 NPs in an organic solvent, then adding Ad-HEMA, stirring at room temperature for 22-26 hours, then adding a polymer compound, stirring at 75-200°C for 20-40 minutes, then standing for 8-12 hours, and finally drying at 150-200°C for 6-12 hours to obtain a polymer blend; the mass ratio of the CD-Al2O3 NPs, Ad-HEMA and the polymer compound is 1-5:4-8:10-15; S5, mixing the polymer blend and polypropylene in a mass ratio of 1-5:10-15, stirring at 180-250° C. for 10-30 min, then standing for 3-5 h, and finally drying at 60-120° C. for 12-24 h to obtain a polymer composite; S6, mixing the polymer composite and the anti-ultraviolet shielding agent evenly, then heating to 60-90°C, adding ammonium sulfate solution and stirring to react for 30-60 minutes, and finally drying at 200-280°C for 10-14 hours to obtain a self-healing intermediate; the ratio of the polymer composite, the anti-ultraviolet shielding agent and the ammonium sulfate solution is 10-20g:1-3g:30-50mL; S7. The self-healing intermediate, the vulcanizing agent and the vulcanization accelerator are mixed in a mass ratio of 2-3:4-6:1-2, and then reacted at 180-200° C. for 10-30 min to obtain a self-healing material.

2. The method for preparing the self-healing material for photovoltaic cables according to claim 1, characterized in that: The base is NaOH or KOH.

3. The method for preparing the self-healing material for photovoltaic cables according to claim 1, characterized in that: The organic solvent is dimethyl sulfoxide or N,N-dimethylformamide.

4. The method for preparing the self-healing material for photovoltaic cables according to claim 1, characterized in that: The inert gas is nitrogen or argon.

5. The method for preparing the self-healing material for photovoltaic cables according to claim 1, characterized in that: The polymer compound is at least one of polyvinyl pyrrolidone, hydroxyethyl methacrylate, acrylate, ethylene glycol dimethacrylate, azobisisobutyronitrile, ethylene-vinyl acetate copolymer, polyether polyol and polyolefin elastomer.

6. The method for preparing the self-healing material for photovoltaic cables according to claim 1, characterized in that: The anti-ultraviolet shielding agent is TiO2, ZnO, SiO2 or CeO2.

7. The method for preparing the self-healing material for photovoltaic cables according to claim 1, characterized in that: The concentration of the ammonium sulfate solution is 0.013-0.1 mol / L.

8. The method for preparing the self-healing material for photovoltaic cables according to claim 1, characterized in that: The vulcanizing agent is benzoyl peroxide or diethyl propyl benzene peroxide; the vulcanization accelerator is trimethylolpropane trimethacrylate or tetramethylthiuram disulfide.

9. A self-healing material, characterized in that: The self-repairing material for photovoltaic cables is prepared by the method for preparing the self-repairing material for photovoltaic cables according to any one of claims 1 to 8.

10. Use of the self-healing material according to claim 9 in the preparation of photovoltaic cables.